2015
DOI: 10.1007/s11273-015-9439-x
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of temperature variance to determine inundation state of wetlands

Abstract: Monitoring the inundation state (wet or dry) of wetlands is critical to understanding aquatic community structure but can be costly and laborintensive. We tested the ability of temperature data from cost-effective iButton data loggers to reflect the inundation state of wetlands in central Missouri, based on our hypothesis that dry ponds would show greater daily temperature variance than ponds that remained inundated with water. We evaluated this method with two experiments in large outdoor mesocosms, and in ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Upon fitting three-state HMMs to the pond-only data set, we found that a threshold between 2.9°C and 3.3°C minimized the number of false dry states for most ponds (Tables S2 and S3). This threshold is slightly lower than that proposed by Anderson et al (2015), who determined that using daily temperature variances cutoffs between 13 and 15 (corresponding to tSDs between 3.6°C and 3.9°C) for the wet state provided the most accurate predictions of pond inundation states in their field experiments. Within our pond-only data set, using a less conservative tSD threshold of 3.5°C decreased the accuracy leading to a false wet state prediction for pond T15U.…”
Section: Comparison Of Two-versus Three-state Hidden Markov Models and Determination Of Wet State Threshold Valuesmentioning
confidence: 62%
See 1 more Smart Citation
“…Upon fitting three-state HMMs to the pond-only data set, we found that a threshold between 2.9°C and 3.3°C minimized the number of false dry states for most ponds (Tables S2 and S3). This threshold is slightly lower than that proposed by Anderson et al (2015), who determined that using daily temperature variances cutoffs between 13 and 15 (corresponding to tSDs between 3.6°C and 3.9°C) for the wet state provided the most accurate predictions of pond inundation states in their field experiments. Within our pond-only data set, using a less conservative tSD threshold of 3.5°C decreased the accuracy leading to a false wet state prediction for pond T15U.…”
Section: Comparison Of Two-versus Three-state Hidden Markov Models and Determination Of Wet State Threshold Valuesmentioning
confidence: 62%
“…A rapid drop in daily temperature variance can reliably measure the precise timing of an inundation event (Anderson et al, 2015;Arismendi et al, 2017). For example, Anderson et al (2015) tested the ability of temperature sensors to accurately predict inundation states both in natural wetlands and in controlled mesocosms that varied in size and depth. The authors deployed temperature sensors for two 6-month periods in ponds over a 7,140 ha area.…”
mentioning
confidence: 99%
“…Corrosion of untreated sensors and wire connections, over several weeks, increased failure rates during rain (Supporting Information Section 3.2). For all sensor types, moisture damage presents a problem, sometimes causing high failure rates (Anderson et al., ; Ashcroft & Gollan, ; Lebrija‐Trejos et al., ; Lewkowicz, ). The failure rate in our study (11.4%) was comparable to those of commercial sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Incorporating measurement capabilities for additional environmental variables such as light or soil moisture increases costs to $500–1000/unit (Table ). In addition, commercial data loggers often fail permanently in field conditions, with reported failure rates of 7%–27% (Anderson et al., ; Ashcroft & Gollan, ; Lebrija‐Trejos, Pérez‐García, Meave, Poorter, & Bongers, ; Lewkowicz, ). Many do not have replaceable batteries or parts or cannot be repaired, thus limiting their life spans.…”
Section: Introductionmentioning
confidence: 99%
“…Our field testing has allowed us to identify several areas in which our DIY soil temperature data logger could be improved in future iterations to increase reliability. Commercial data loggers experience failures in the field with reported failure rates of 7–27% per year [ 20 , 36 , 37 , 38 , 39 ]. The majority of our data logger failures were due to leaks.…”
Section: Discussionmentioning
confidence: 99%